Capturing the Benefit of Groundwater for Water Resources Sustainability - REJEKININGRUM, POPI (Indonesian Center for Agriculture Land Resource Development, 2009)
Groundwater is the water contained in soil or rock layer below the surface. Ground water is one of the limited water resources and the damage can give a broad impact, whereas its recovery is difficult. In addition to river water and rain water, ground water also has a very important role, especially in maintaining the balance and availability of raw water for domestic or industrial purposes. In some areas, dependency on fresh water and ground water supplies has reached Â± 70%. Lack of understanding on groundwater condition that occurred in the community, arises problems that become the lost and threaten to life sustainability of the community itself. It is necessary for planning the utilization of groundwater that environmentally oriented based on the stage that includes an inventory of potential groundwater, utilization planning, licensing, monitoring and controlling, and conservation of groundwater. Inventoring of potential groundwater utilization planning, licensing, monitoring and controlling should be based on existing procedures so that utilization can be optimized without causing negative impacts.